Stationary equilibria in bargaining with externalities - Jonas Björnerstedt; Andreas Westermark (Uppsala University, Department of Economics, 2008)
This paper studies infinite-horizon bargaining between a seller and multiple buyers when externalities are present. We extend the analysis in Jehiel & Moldovanu (1995a) by allowing for both pure and mixed equilibria. A characterization of the stationary subgame perfect equilibria in generic games is presented. Equilibria with delay exist only for strong positive externalities. Since each buyer receives a positive payoff when the seller makes an agreement with some other buyer, positive externalities induce a war of attrition between buyers.
urn:nbn:se:uu:diva-211154
Keywords: C72; C78; D62; 330; ANC; Bargaining; externalities; delay